Are the Poor Protected from Budget Cuts? Theory and Evidence for Argentina - Ravallion, Martin (World Bank, Washington, DC, 2015)
Adjustment programs often emphasize protecting social spending - especially pro-poor spending - from cuts. Yet the incidence of fiscal contraction - and hence the case for action to protect public spending on the poor at a time of overall fiscal austerity - is an empirical question, which the author addresses using data from Argentina. Aggregate budget cuts in Argentina in the 1980s and 1990s, typically brought proportionately greater cuts in social spending. "Non-social" spending was protected. But proportionate cuts for types of social spending that matter more to the poor, were about the same as the cuts for those that tend to favor the non-poor. Absolute cuts were in fact greater for "social insurance" that matters more to the non-poor. But spending on targeted social assistance, and employment programs, was more vulnerable to aggregate spending cuts, than were more universal social services. Social spending was clearly exposed to fiscal contraction, but this was somewhat less true of pro-poor spending on things that also benefited the non-poor. So fine targeting may be a mixed blessing for the poor, bringing greater vulnerability to cuts, possibly when help is most needed. There is a strong case for action to protect pro-poor social spending at such times. An externally financed work-fare scheme in Argentina was far better targeted than other social spending, but still had to ensure that a small, but relatively well-protected share of the benefits went to the non-poor. The program was clearly subject to the same political economy constraints that influenced the incidence of past fiscal contractions in Argentina. The program expanded into poor areas when the budget increased, but retreated from poor areas when the program was cut. It was the program's disbursements to non-poor areas that were protected. Still, given the low wage rate offered, the direct benefits from the program were still likely to have favored the poor, even after the cuts.